2003
DOI: 10.1007/s00247-003-1009-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening of the lambdoid suture in the child with posterior plagiocephaly

Abstract: Sonography of the lambdoid sutures shows excellent preliminary promise as a screening test of lambdoid sutural patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…Previous studies evaluating the accuracy of CUS for evaluation of the cranial sutures have compared CUS with CT. 15,16,18,19,21,23,24 Regelsberger et al 16 reported 100% success of CUS in the detection of craniosynostosis in 26 patients proven to have this condition on CT. Sze et al 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluating the accuracy of CUS for evaluation of the cranial sutures have compared CUS with CT. 15,16,18,19,21,23,24 Regelsberger et al 16 reported 100% success of CUS in the detection of craniosynostosis in 26 patients proven to have this condition on CT. Sze et al 24 …”
Section: Discussionmentioning
confidence: 99%
“…16,18,19,21,23,24 The lack of a larger series comparing findings of CUS with plain radiographs in this setting may be partly responsible for the underutilization of CUS as a first imaging tool for the detection of craniosynostosis.…”
mentioning
confidence: 99%
“…Normal and abnormal sonographic appearance of the cranial sutures in infants was described by Soboleski at al., who showed excellent correlation between histological section, plain radiograph, CT, and MRI findings [7,8]. Ultrasound has been shown to be effective for evaluation of posterior plagiocephaly [16,17]. US evaluation of the cranial sutures is relatively simple technically in a newborn, but can be challenging in older babies due to head motion, more head hair, and narrower sutures.…”
Section: Discussionmentioning
confidence: 92%
“…10 Some authors advocate for the use of ultrasound as a way of screening for the patency of sutures in cases of plagiocephaly. 4,7,11,12 Hyperechoic fusion of bones and ridging are characteristic aspects of suture synostosis. 6 It is with this background that we applied ultrasound to try and identify more precisely the lambda in infants undergoing minimally invasive endoscopy-assisted craniectomies for sagittal synostosis.…”
Section: Discussionmentioning
confidence: 99%